A highly efficient preconcentration route for rapid and sensitive detection of endotoxin based on an electrochemical biosensor. Issue 12 (27th May 2020) - Ma, Wenrui; Liu, Lulu; Xu, Yi; Wang, Li; Chen, Li; Yan, Sheng; Shui, Lingling; Wang, Zhijun; Li, Shunbo
Abstract : A microfluidic biosensor was designed for rapid and highly sensitive detection of endotoxin, which could be detected within 0.5 h and with a detection limit of 0.5 ng mL −1 . Abstract : An impedimetric aptasensor for the detection of endotoxin in a microfluidic chip was proposed, in which the Apt/AuNPs/SPCE sensing surface was fabricated in a screen-printed electrode with good biological activity and stability. The quantitative detection of endotoxin was accomplished by electrochemical impedance spectroscopy (EIS) measurement before and after exposing to samples. The impedance biosensor offers an ultrasensitive and selective detection of endotoxin down to 500 pg mL −1 with a wide linear range from 500 pg mL −1 to 200 ng mL −1 . According to the Langmuir isotherm model, the interactions between the target molecules and the sensing surface had been analyzed and strong binding was concluded. Compared to the traditional static incubation methods, the microfluidic biosensor realizes the enrichment of endotoxin owing to the confined space and continuous flow nature, so that the lowest detection concentration is reduced from 5 ng mL −1 to 500 pg mL −1, which is much lower than the existing technology, and the total assay time is shortened from 1.0 h to 0.5 h. The proposed microfluidic impedance biosensor provides a new strategy for the design of an aptasensor to realize the rapid detection of target biomolecules with high sensitivity and it can be integrated into wearable medical devices due to its flexible properties.